PHILOSOPHICAL AND PEDAGOGICAL BASES OF PATRIOTIC EDUCATION IN THE WORKS OF G. VASHCHENKO - Holovchuk, Svitlana Y. (Educological discourse, 2014)
The article deals with the philosophical and pedagogical foundations of patriotic education in the works of G. Vashenko; based on a holistic retrospective analysis of psycho-pedagogical Heritage and Activities G. Vashenko generalized his ideas about the Ukrainian patriotic education as a goal of national pedagogy, considered them combined achievements of European philosophical and educational thought with the achievements of Ukrainian folk pedagogy.